CPM, PERT and Project Management With Fuzzy Logic Technique and Implementation On A Business - Mazlum, Mete; Guneri, Ali Fuat (ELSEVIER SCIENCE BV, 2015)
As a result of increased competition environment, it has been obligatory to complete the projects in the foresighted time and with the specified sources. An effective project management is necessary to finish the projects without delay and with the available qualifications identified beforehand. The project planning techniques are utilized to satisfy these necessities. In this study, classic PERT and CPM, which are project management techniques, fuzzy PERT and fuzzy CPM, which are used in the fuzzy project management, will be used to improve an online internet branch and to plan the project of an online internet branch. At the end of the study, the results will be analyzed. In the study, certain and fuzzy activity times of three different firms are used. With certain activity times, classic CPM and PERT optimization and with using triangular fuzzy numbers for fuzzy data, CPM and PERT optimization are analyzed.
Keywords: Project Management; Fuzzy Logic; PERT; CPM; Fuzzy PERT; Fuzzy CPM; CRITICAL PATH; Business & Economics; Social Sciences - Other Topics